GAMBARAN PENGETAHUAN IBU TENTANG PIJAT OKETANI DALAM MENINGKATKAN PRODUKSI ASI DI PMB BIDAN C KOTA BANDUNG - Safitri, Laili; Rahmawati, Naili; Indriati, Maya (Universitas Batam, 2021)
Mother's milk (ASI) is an emulsion of fat in a solution of protein, lactose and inorganic salts secreted by the mother's mammary glands, and serves as food for babies, therefore, in increasing milk production, several things can be done. One method is by doing oketani massage. Oketani massage is a massage that does not cause pain. It can stimulate muscle strength making it easier for babies to suck breast milk. To know the level of knowledge of pregnant women in the third trimester of understanding, knowledge of characteristics, knowledge of effectiveness, knowledge of benefits, and knowledge of the steps of oketani massage at PMB Midwife C, Bandung City. Research This study used descriptive research. Location at PMB Midwife C Bandung in March-April 2021. Accidental sampling technique as many as 37 respondents. Data analysis used univariate analysis with statistical tests. Most of the third trimester pregnant women have a level of knowledge about oketani massage into the sufficient category as many as 25 people (67.6%). Most of the third trimester pregnant women have a level of knowledge about oketani massage into the sufficient category at PMB Midwife C Bandung City